Water redistribution among various sectors to avoid freezing of air-cooled heat exchanger. (October 2019) - Kong, Yanqiang; Wang, Weijia; Yang, Lijun; Du, Xiaoze; Yang, Yongping
Highlights: Circulating water redistribution among various sectors is proposed for anti-freezing. Water flow rate of the frontal sector increases with increasing the wind speed. At low wind speeds, water flow should not decrease more for middle and rear sectors. Middle and rear sectors cannot freeze with low water flow rates at high wind speeds. Abstract: In extremely cold days, the freezing risk of air-cooled heat exchanger has been a great concern for natural draft dry cooling system in power plants. In this work, the circulating water redistribution among various sectors is proposed and analyzed at different wind speeds against the equal water flow distribution mode, by which both the anti-freezing and energy-efficient operation demands of natural draft dry cooling system are satisfied. The results show that at the low wind speed of 4 m/s, the water flow rates of the middle and middle rear sectors should not decrease too much in case of the unexpected freezing risks. However, at the high wind speeds of 12 m/s and 16 m/s, they face no freezing risks due to the extremely low cooling capacity of ambient air. As a result, these two air-cooled sectors can be dismissed at high wind speeds for a better energy efficiency. By directing the circulating water of the middle and middle rear sectors to others, not only the serious freezing risks of the sectors can be avoided, but the economic operation of natural draft dry cooling system can also be achieved.